Novel stereocontrolled syntheses of tashiromine and epitashiromine - Kiss, Loránd; Forró, Enikő; Fülöp, Ferenc (Beilstein Journal of Organic Chemistry, 2015)
A novel stereocontrolled approach has been developed for the syntheses of tashiromine and epitashiromine alkaloids from cyclooctene β-amino acids. The synthetic concept is based on the azetidinone opening of a bicyclic β-lactam, followed by oxidative ring opening through ring C–C double bond and reductive ring-closure reactions of the cis- or trans-cyclooctene β-amino acids.
Keywords: alkaloids; amino acids; ring closure; ring opening; stereocontrolled synthesis